Hire Me, I Trust You! Perceived Organizational Trustworthiness and the Effect of CSR Activities on Job Pursuit Intentions - AQUEVEQUE TORRES, CLAUDIO ALBERTO; Ignacio J. Duran; P. Rodrigo (Wiley, 2025)
ABSTRACTWhile research studying the effect of CSR on prospective employees is common, virtually all works utilize similar explanations and underpinnings. Utilizing signaling theory and social identity theory to coin the “good working condition hypothesis,” we propose a new underlying mechanism—perceived organizational trustworthiness—to reassess why responsible companies attract prospective employees. We also distinguish between internal‐external CSR and perceived CSR‐fit as boundary conditions to explore this phenomenon further. Using an experimental design in a large sample (n = 517), we conjecture a mediated‐moderated model to test our assertions. Findings show that perceived organizational trustworthiness fully mediates the link between external CSR and job pursuit intentions, but only in the presence of low/medium perceived CSR‐fit. Contrarily, in the presence of high perceived CSR‐fit, it is internal CSR that increases perceived organizational trustworthiness and job pursuit intentions.